Direct electrophilic N-trifluoromethylthiolation of amines with trifluoromethanesulfenamide - Alazet, Sébastien; Ollivier, Kevin; Billard, Thierry (Beilstein Journal of Organic Chemistry, 2013)
The CF3SN moiety is a substituent with interesting properties. However, there is no easy synthetic access to molecules bearing this group. The trifluoromethanesulfenamide is a new reagent for the electrophilic trifluoromethylthiolation which reacts easily with amines to obtain trifluoromethylsulfanylamines with good yields.
Keywords: amine; fluorine; organo-fluorine; trifluoromethanesulfenamide; trifluoromethylsulfanylamine; trifluoromethylthiolation